Periodontal disease as the initial oral manifestation of abdominal tuberculosis - Mukhatar Ahmed Javali; Vishwanath Patil; Humera Ayesha (Wolters Kluwer Medknow Publications, 2012)
Tuberculosis is a chronic, specific granulomatous disease and a major cause of death in developing countries. We report a case of tuberculosis presenting first as periodontal loss of tooth support leading to loose teeth and gingival enlargement affecting a 17-year-old female patient without any pulmonary lesion. Diagnosis was based on histopathological examination and positive adenosine deaminase activity Mycobacterium tuberculosis test. The clinical presentation of tuberculosis may take many forms. However, with the decline in numbers, tuberculosis lesions of the oral cavity have become so rare that they are frequently overlooked in the differential diagnosis of oral lesions. Also, this case report emphasizes the need for dental clinicians to be aware of the possibility of tuberculosis presenting first in the oral cavity, and contribute in control of tuberculosis through early detection and referring the patients to physicians for proper treatment.